2013
DOI: 10.5539/esr.v2n2p93
|View full text |Cite
|
Sign up to set email alerts
|

The Origin of Etch Pits Recorded on Residual Grain Surfaces from Kaolinized Granitic Rocks West Region Cameroon

Abstract: The weathering of some granitic rocks in the West Region of Cameroon (Central Africa) was examined by X-ray diffraction (XRD) and X-ray fluorescence Spectrometer (XRF) in conjunction with Scanning Electron Microscopy (SEM). Kaolinite and illite were the most predominant weathering products whereas gibbsite, goethite and maghemite were also found in small amounts; only residual quantities of quartz and potassium feldspar were observed. The geochemical study shows the mobility of major elements during the progre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…Nesbitt and Young (1982, 1984, 1989 and Nesbitt et al (1996) used ternary A-CN-K and A-CNK-FM diagrams to deduce weathering trends. These authors demonstrated that the bulk compositions of diverse rocks composition follow simple trends that are largely unaffected by the climatic conditions under which weathering took place (Aristizábal et al, 2005;Wouatong et al, 2013). In addition to providing a method of visualizing the degree of weathering, the A-CN-K system permits the evaluation of the weathering trends from fresh rock compositions through their weathering products (Fedo et al, 1995;Aristizábal et al, 2005;Wouatong et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Nesbitt and Young (1982, 1984, 1989 and Nesbitt et al (1996) used ternary A-CN-K and A-CNK-FM diagrams to deduce weathering trends. These authors demonstrated that the bulk compositions of diverse rocks composition follow simple trends that are largely unaffected by the climatic conditions under which weathering took place (Aristizábal et al, 2005;Wouatong et al, 2013). In addition to providing a method of visualizing the degree of weathering, the A-CN-K system permits the evaluation of the weathering trends from fresh rock compositions through their weathering products (Fedo et al, 1995;Aristizábal et al, 2005;Wouatong et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Chemical weathering indices based on quantitative measurements based on whole-rock chemical analyses are commonly used to characterize the intensity and mechanisms of weathering (Nesbitt and Young, 1982;Irfan, 1996Irfan, , 1999Ng et al, 2001;Gupta and Rao, 2001;Voicu and Bardoux, 2002;Aristizábal et al, 2005;Wouatong et al, 2013). Recent works have shown that weathering indices based on the ratio of a group of mobile elements to one or more immobile elements are useful parameters for characterizing changes induced by weathering (Duzgoren-Aydin et al, 2002;Aristizábal et al, 2005;Wouatong et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations